2023
DOI: 10.2478/aiht-2023-74-3648
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of resveratrol against fumonisin B1-induced liver toxicity in mice

Abstract: The aim of this study was to investigate the effects of resveratrol against fumonisin B1 (FB1)-induced liver toxicity, as, to the best of our knowledge, these effects have not been investigated yet, even though the toxic effects and mechanisms of FB1 and the antioxidative effects of resveratrol are well known. 40 BALB/c mice were divided into control, FB1, resveratrol, and FB1+resveratrol groups. Control received saline for 14 days. The FB1 group received 2.25 mg/kg FB1 every other day for 14 days. The resvera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…At the end of the experiment, we firstly analyzed whether acacetin showed potential toxicities in animals. Serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) have been used as major biomarkers for liver damage, especially as biomarkers for substances-induced liver toxicity 17 , 18 . We found that 10 mg/kg acacetin showed no effect, while 20 mg/kg acacetin significantly reduced the serum levels of ALT and AST (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the end of the experiment, we firstly analyzed whether acacetin showed potential toxicities in animals. Serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) have been used as major biomarkers for liver damage, especially as biomarkers for substances-induced liver toxicity 17 , 18 . We found that 10 mg/kg acacetin showed no effect, while 20 mg/kg acacetin significantly reduced the serum levels of ALT and AST (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This toxicity also becomes much more pronounced with increased adiposity ( 89 ). Nevertheless, a recent study showed that these adverse effects can be mitigated when resveratrol is co-administered, as this polyphenol acts as an hepato-protector ( 90 ).…”
Section: Experimental/clinical Evidence Of Therapies Targeting Sphing...mentioning
confidence: 99%